2010
DOI: 10.5897/ajb10.859
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic appraisal effects of straw extract wheat varieties on the growth of corn

Abstract: Allelopathy is a process in which secondary metabolites produced by plants, micro-organisms, viruses and fungi control growth and development of other biological systems. Some plants may beneficially or antagonistically affect other plants through allelochemical compounds which may be released directly or indirectly from live or dead parts and cause allelopathic and phytotoxic effects. In Kerman province of Iran, cultivating corn after winter wheat usually causes less growth and yield, hence, this study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The heterophile/lymphocyte ratio showed a 55% reduction when β-mannanases were provided compared to when the diet lacked the enzyme, as previously reported [ 28 , 29 ]. A reduction in this parameter has been associated with increased immunity, which is likely attributable to the reduction in stress among the broilers.…”
Section: Discussionsupporting
confidence: 85%
“…The heterophile/lymphocyte ratio showed a 55% reduction when β-mannanases were provided compared to when the diet lacked the enzyme, as previously reported [ 28 , 29 ]. A reduction in this parameter has been associated with increased immunity, which is likely attributable to the reduction in stress among the broilers.…”
Section: Discussionsupporting
confidence: 85%
“…This may also be the result of a decrease in the viscosity of intestinal content. Reducing the viscosity of intestinal content can increase the length and width of the villi and subsequently increase their surface area ( Mehri et al, 2010 ). The obtained results may indicate that FRSM can be an energy and building material for intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…Daskiran et al ( 28 ) demonstrated that diets that used β-mannanase significantly reduced the water of total fecal production in broilers. Likewise, Mehri et al ( 29 ) demonstrated that the viscosity of digesta from the jejunum of broiler chickens decreased in diets with the enzyme. The cleaner eggs observed in the probiotic treatment can likely be attributed to the enhanced stability of the intestinal microbiota and lower count of opportunistic bacteria.…”
Section: Discussionmentioning
confidence: 96%